GENERAL CHARACTERISTICS OF FLORA IN PROJECTED NATURAL PARK BELOKURIKHINSKIY - Elesova, N. V.; Ovcharova, N. V.; Silanteva, M. M. (Acta Biologica Sibirica, 2016)
The article presents the results of field geobotanical and floristic studies conducted during 2015-2016. It was revealed that special conservation value have the chern, pine, and birch forests on granite, pine forests with nemoral elements, meadow steppes, alkaline fen meadows with grouse, mezopetrofiton.